2016
DOI: 10.3133/sir20165030
|View full text |Cite
|
Sign up to set email alerts
|

Perchlorate and selected metals in water and soil within Mount Rushmore National Memorial, South Dakota, 2011–15

Abstract: The observed deposition of firework debris within Lafferty Gulch drainage basin coupled with the lack of alternative perchlorate sources indicates that past firework displays are the most probable source of perchlorate contamination. from shells that do not launch from the mortar (Massachusetts Department of Environmental Protection, 2007). Fallout of fine particulates is thought to occur in a uniform manner, whereas deposition of shell fragments and debris are irregular and are dependent on wind conditions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The NPS completed a geologic resource evaluation report of the memorial in 2008 (Graham, 2008). From 2011to 2015, Hoogestraat and Rowe (2016 investigated perchlorate and selected metals in wells, springs, surface waters, and soils at the memorial.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The NPS completed a geologic resource evaluation report of the memorial in 2008 (Graham, 2008). From 2011to 2015, Hoogestraat and Rowe (2016 investigated perchlorate and selected metals in wells, springs, surface waters, and soils at the memorial.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The hydrogeology of the memorial includes localized and noncontinuous aquifers composed of unconsolidated Quaternary alluvial deposits and consolidated Proterozoic igneous and metamorphic bedrock (Powell and others, 1973;Hoogestraat and Rowe, 2016). Groundwater in the alluvial aquifers is affected by the hydrologically connected stream waters in the drainages of the memorial.…”
Section: Hydrogeologymentioning
confidence: 99%
See 1 more Smart Citation
“…Other constituents in fireworks, such as barium, strontium, copper, and other metals, also have the potential to cause contamination, but as the regulatory limits for these compounds in water are much higher than perchlorate, the deposition of these constituents is much less likely to be of environmental concern. A study of groundwater contamination by perchlorate and metals from fireworks at Mount Rushmore National Memorial detected a maximum perchlorate concentration of 35 μg/L in groundwater but did not detect elevated concentrations of metals in groundwater (Hoogestratt and Rowe 2016). Groundwater contamination from fireworks in Dartmouth, Massachusetts is described by MassDEP (2007) where a maximum concentration of 62 μg/L was detected in groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively these papers clearly showed that residuals from fireworks can result in increased concentrations of perchlorate in surface water and groundwater. The perchlorate that leaches to groundwater is mobile and persistent under aerobic conditions (Hoogestratt and Rowe 2016).…”
Section: Introductionmentioning
confidence: 99%